Treatment of Chronic Migraine: A 3‐Month Comparator Study of Naproxen Sodium vs SumaRT/Nap. Issue 1 (10th September 2013) - Cady, Roger; Nett, Robert; Dexter, Kent; Freitag, Fred; Beach, M.E.; Manley, Heather R.
<x xml:space="preserve">Abstract</x> Objective To compare the use of a combination of 85 mg sumatriptan plus 500 mg naproxen sodium in a combination tablet with 500 mg naproxen sodium in an identically appearing tablet when used as a daily preventative and acute treatment for 1 month and episodic acute treatment for an additional 2 months in patients with chronic migraine. Background To date, there has been minimal study of acute medications for patients with chronic migraine. Consequently, there is a paucity of study methodology or evidence‐based guidance on the use of acute treatment medications in patients with chronic migraine. Methods This two‐center, double‐blind, randomized, parallel‐group, comparator pilot trial of 28 subjects, 18 to 65 years of age, with ICHD‐II defined chronic migraine, was designed to generate hypotheses about the efficacy of 2 established acute migraine medications used both as a daily preventive treatment (month 1) and episodic acute treatment (months 1, 2, and 3). Subjects were randomized 1:1 to treat daily with SumaRT/Nap (85 mg sumatriptan + 500 mg naproxen sodium) (group A) or naproxen sodium (500 mg) (group B) in a prophylactic strategy for 1 month followed by 2 months of the same medications used for episodic acute treatment. Results The combination of SumaRT/Nap used over a 3‐month period did not appear to significantly reduce the number of migraine headache days. In the subset of subjects using naproxen sodium and completing the study per protocol, there was a marked reduction in migraine headache days (P < .02 vs 0.25, respectively). Duration of migraine from treatment to pain free decreased in both groups, but was more robust in group B from baseline to month 3. Subjects in group B completing the study per protocol reported a 56% reduction in headache days vs 8% for group A. Subjects in group A and group B completing the study per protocol had considerably better 2‐hour headache relief than subjects withdrawing early from the study. More subjects in group B prematurely withdrew from the study because of lack of efficacy (5 vs 1, respectively). Despite using significant quantities of acute medication during month 1, there was a reduction of acute medication in month 2 and 3 vs baseline vs month 1, particularly in the naproxen group. Conclusion A combination of SumaRT/Nap (group A) did not appear to reduce migraine headache frequency over a 3‐month period. Subjects using naproxen sodium (group B) alone and completing the study per protocol had a marked statistically significant reduction in migraine headache days. Both groups completing the study per protocol had experienced clinically meaningful 2‐hour headache relief. This suggests there may be a subset of patients with chronic migraine that are responsive to high doses of naproxen as an acute intervention with a significant prophylactic benefit. Subjects randomized to SumaRT/Nap experience benefit, primarily as an acute intervention. This hypothesis may warrant future larger scale clinical trials. Frequent dosing of SumaRT/Nap or naproxen sodium was well tolerated in this study.